THE MILK PRODUCTION OF HUNGARIAN GREY CATTLE IN THE RESPECT OF THE COMPOSITION OF COLOSTRUM - A. Z. Kovács (Poljoprivreda, 2000)
The ancient Hungarian Grey Cattle was famous in Europe for a thousand years until the 20th century. The fame is due to its meat of excellent flavour and mottling texture. However, this cattle type did not meet the milk production requirements of the 20th century because of its low milk yield, and therefore lost dominance from the beginning of the 1900’s, playing only the role of gene bank since the sixties. Considering that its gene base is ideal if crossed with beef cattle and the lack of detailed information on its colostrum and milk composition because of contemporary laboratory techniques, the author tries to fill the gap in this respect in his researched work. The number of colostrum samples was n = 19. The dry matter (31.00 %) the protein (20.90 %) and the lactose content (4.49 %) of the first milked colostrum is overdue surpasses those of all of the cattle types, which were cited in the professional literature by some authors. The only component of the first milked colostrum which the Hungarian Grey Cattle stay beyond of the other beef types is the fat content (4.46